DISTRIBIÇÃO GEOGRÁFICA E AUTOECOLOGIA DE MORCEGOS HEMATÓFAGOS Diaemus youngi (Jentik, 1893) E Diphylla ecaudata (Spix, 1823) (MAMMALIA: CHIROPTERA) NOS BIOMAS BRASILEIROS - DIAS, Rivael Rocha,; DIAS, Rosa Maria,; PEREIRA DA SILVA, Elifas Augusto,; ORTÊNCIO-FILHO, Henrique,; KASHIWAQUI, Elaine Antoniassi Luiz, (ANAIS DO ENIC, 2025)
.